College Students' Religious Beliefs, Knowledge of Evolution, and Science Literacy : Comparisons by Sex, Discipline, and Point of College Career - Fuerstenberg, Eric; Ryan, Danielle; Miller, Stacy; Harris, Heather D.; Risdal, Megan; Byrne, Brittany L.; Camp, Sarah E.; Ritchie, Laura (My University, 2011)
If being in college promotes science literacy and critical, evidence-based thinking, then college seniors should demonstrate higher levels of scientific knowledge and lower levels of religious belief than should freshmen. Among seniors, those in Math & Natural Sciences should score higher in science literacy than should those in other disciplines. The current study was designed to test these predictions.
Color poster with text, graphs, and tables.
Keywords: Religiousness; College freshmen--Knowledge--Science; College seniors--Knowledge--Science; College students--Knowledge--Science--Sex differences; College discipline; Posters